La restricción aspectual de la telicidad en la construcción atributiva de resultado. - Rodríguez Arrizabalaga, Beatriz (Estudios Ingleses de la Universidad Complutense, 2000)
In the vast literature on the English resultative construction it has been constantly shown that the appearance of the resultative attribute is highly limited (Bolinger 1971; Rothstein 1983; Simpson 1983; Tenny 1987; Bresnan and Zaenen 1990; Goldberg 1991, 1995; Levin and Rappaport 1992, 1995). Surprisingly, however, none of the aforementioned linguists, except Goldberg within the theoretical frame of Construction Grammar, have accounted the co-occurrence restrictions of such an element. Proposing an alternative to Goldberg's Unique Path Constraint, our main objective in the present paper is to explain in aspectual terms the constrained appearance of the resultative attribute. We claim that such a grammatical constituent, being a telic marker, cannot surface in any clause that is either lexically or syntactically bounded. In this way, we prove in the realm of the English resultative pattern Tenny's aspectual hypothesis that telicity is lexically and/or syntactically determined by the presence of solely one delimiting element. 1.